Discovering How to Do Reflexivity and Self-Reflexivity: A Longitudinal Empirical Research Findings - de Verlaine, Emmanuelle (Advances in Social Sciences Research Journal, 2022)
Reflexivity is known to be a mental process where a person takes distance to oneself to analyze and take a critical perspective over own feelings, actions and intentions in order to realign own practice. Reflexivity is therefore a form of metacognitive brain functionality reaching a state of mind’s sense of acute awareness. The reflexivity’s functionality has been recognized as valuable to improve professional practices. The main gap in research and literature is to explicate how to do reflexivity and most of all, how to apply it to all aspects of human life toward self-actualization. This research aims at answering at: How to Do reflexivity and Self-Reflexivity? To answer this question a 17 year-long longitudinal Action-Research investigations reveals how to learn and practice reflexivity. This paper also reveals how reflexivity can be applied to aim at one’s well-being and self-actualization. The discussion addresses the long-term impact of practicing reflexivity coupled with mindfulness as an ability to reach self-liberation.